Case report: Extreme respiratory sinus arrhythmia in a non-athlete female student - a peculiar finding at the Physiology practicum - Karemaker, John M. (Frontiers in Neuroscience, 2024)
During an ECG-training course, a case of extreme respiratory sinus arrhythmia (RSA) was found in a 19-year-old slender, female student who was not active in sports. The heart rate (HR) fluctuated from above 100 to below 60 beats per minute (bpm), often from one beat to the next. The pattern was repetitive and appeared to be linked to respiration, representing an extreme form of RSA. The initial recording of the HR and blood pressure (BP) by finger blood pressure showed concomitant drops in diastolic BP of up to 25 mmHg. The student agreed to participate in a short follow-up study, during which HR, BP, and respiration (measured by temperature and pCO2 of the airflow at the nose) were recorded in the supine and upright tilted positions. Measurements were taken during 5 min of rest, during paced breathing (1 min each at 6, 10, and 15 breaths per min), and during end-expiratory breath-hold. This study presents a beat-by-beat analysis of the observed interrelations between respiration, HR, and BP. Her respiratory rate with maximal RSA was found to be only slightly lower than the spontaneous rate, at 10 versus 12 breaths per min. From the combined observations, it was concluded that, in this case, the baroreflex relationship between spontaneous BP and HR changes was overridden by near on/off gating of (possibly massive) cardiac vagal outflow. This is due to a central, respiration-coupled gating mechanism, with the vagus nerve being “on” during expiration and “off” during inspiration. Such a system will destabilize blood pressure. It shows an evolutionary remnant of optimizing lung perfusion during air inflation, regardless of the consequences for systemic blood pressure.